Deradicalization Through Pancasila Moral Education in Indonesia - Kristianto, Tri Agus (Journal of Creativity Student, 2018)
Deradicalisation is every effort to neutralize radical ideals through interdisciplinary approaches, such as law, psychology, religion, economics, education, humanity and socio-culture for those who are influenced or exposed to radical and / or pro-violence. Implementation of Deradicalization Program (Development) can be done through Deradicalization in Prisons with the Target of terrorism prisoners who are in prison by identifying, Rehabilitation, Reeducation and Resosialisation. Deradicalisation has a goal, among other things, to restore the actors involved who have a radical understanding to return to a more moderate mindset. Deradicalisation of terrorism is very important because terrorism has become a serious problem for the international community because at any time it will endanger the national security for the country hence deradicalization program is needed as a formula of prevention and prevention of radical understanding like terrorism.